2018
DOI: 10.1139/juvs-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Public perception of UAS privacy concerns: a gender comparison

Abstract: While much research has examined engineering and practical uses of unmanned aerial systems (UAS), there have been very few studies that have examined privacy concerns that the public may have towards UASs. Even less research has been conducted on how gender and type of UAS mission may affect privacy concerns. This paper examines gender differences in privacy concerns across a wide array of UAS mission types. We also examine potential mediators that explain why females and males differ in their privacy concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Social Challenges Early on, social challenges associated with commercial drones received great attention by academia and multiple studies already analyzed the public perception of drones in the past (e.g., Eißfeldt and End, 2020;Miethe et al, 2020). In this process, researchers repeatedly argue that the acceptance of drones as a new emerging technology will have a major impact on the success of integration and scaling of commercial use (Macias et al, 2019;Rice et al, 2018). The German Aerospace Center conducted a survey in Germany in 2020 with 832 participants on the acceptance of drone deliveries and showed that 59% of the respondents disapprove drone delivery applications.…”
Section: Operational Challenges While Commercial Dronesmentioning
confidence: 99%
See 2 more Smart Citations
“…Social Challenges Early on, social challenges associated with commercial drones received great attention by academia and multiple studies already analyzed the public perception of drones in the past (e.g., Eißfeldt and End, 2020;Miethe et al, 2020). In this process, researchers repeatedly argue that the acceptance of drones as a new emerging technology will have a major impact on the success of integration and scaling of commercial use (Macias et al, 2019;Rice et al, 2018). The German Aerospace Center conducted a survey in Germany in 2020 with 832 participants on the acceptance of drone deliveries and showed that 59% of the respondents disapprove drone delivery applications.…”
Section: Operational Challenges While Commercial Dronesmentioning
confidence: 99%
“…Delivery drones for emergency situations or disaster management received much higher support than commercial parcel deliveries or the transport of people in autonomous air taxis (Aydin, 2019;Lin Tan et al, 2021;Miethe et al, 2020). In general, privacy and safety concerns were mentioned most often to impact public perception (e.g., Macias et al, 2019;Rice et al, 2018). Even though delivery drones do not primarily intend to capture sensitive video data or monitor people, they can impose stress and anxiety since they can easily create a feeling of "being watched" (Jeelani and Gheisari, 2021;Rice et al, 2018).…”
Section: Operational Challenges While Commercial Dronesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that older people are more supportive of the use of drones compared to younger people, especially for rescue and emergency uses [42], [52]. With regard to gender, research has shown that women are less supportive of drone use and more concerned about privacy than men [35], [42], [53]. In contrast, educational levels of interviewees appear to have no effect on their public perceptions of drones [35], [42].…”
Section: Individual Differencesmentioning
confidence: 99%
“…People's perception of how drones impact on their lives varies and is well documented in literature. Privacy is among the strongest concern (Walther et al 2019;Rice et al 2018;Grubesic and Nelson 2020). Under the drone's eye, people are like the prisoner of Michel Foucault's panopticon: "He is seen, but he does not see; he is an object of information, never a subject in communication.…”
Section: Private Surveillance Public Surveillance Mass Surveillancementioning
confidence: 99%